Identifying the main factors involved in business intelligence implementation in SMEs - Juan Alexis Becerra-Godinez; José Leonardo Serralde-Coloapa; Martin Salvador Ulloa-Marquez; Abraham Gordillo-Mejia; Elizabeth Acosta-Gonzaga (Bulletin of Electrical Engineering and Informatics, 2020)
In recent years, the use of information and communication technology (ICT) tools has been recognized as a critical element for the development of enterprises; being mainly exploited by large companies. However, small and medium enterprises (SMEs) have yet opportunities to take advantage of them; this is the case of the implementation and usage of business intelligence (BI), which is a term that encompasses applications, tools, and methodologies that support decision-making process at a managerial level. Nevertheless, so far there is not a clear approach for its adoption in SMEs, for this reason, this work aims to identify the main factors involved in Business Intelligence implementation in SMEs through a literature review. Information for the analysis was gathered from scientific databases. The results showed main factors that influence the adoption of BI technologies in SMEs as well as recommendations given by several authors to ensure success in the process.